Integrative physiological, biochemical, and metabolomic analyses reveal complex drought and zinc stress tolerance in a novel Miscanthus hybrid - Islam, Monirul; Ali, Amjad; Zhang, Leilei; Ferrarini, Andrea; Lucini, Luigi; Clifton-Brown, John; Amaducci, Stefano (Frontiers in Plant Science, 2025)
Stresses caused by drought and heavy metals (HMs) adversely affect the establishment and yield potential of Miscanthus plants. These stresses are particularly acute on lower quality ‘contaminated and marginal-lands’ less suitable for food production. In our prior research assessing drought and zinc stress tolerance across seven novel Miscanthus hybrids, a M. sacchariflorus × M. sinensis hybrid ‘GRC10’ exhibited superior stress tolerance and biomass production. This study investigated the effects of drought (D), zinc (Zn) stress, and their combination (D + Zn) on stress tolerance in the Miscanthus GRC10 using untargeted metabolomics to uncover stress tolerance mechanisms. Synchronous measurements of growth parameters, leaf gas exchange parameters, the maximum quantum yield of photosystem II (Fv/Fm), performance index (PI-ABS), antioxidant enzyme activity, proline, and malondialdehyde (MDA) production were made to elucidate associations. Both D, Zn, and combination (D + Zn) stress induced a broad metabolic reprogramming of secondary metabolism and hormone synthesis pathways. Fatty acid derivatives, nitrogen-containing compounds, hormone/signal-related compounds (jasmonate), and secondary metabolites (phenylpropanoids, N-containing compounds, and terpenes) showed significant (p < 0.05) abundance changes in response to D, Zn, and its combination D + Zn stress. Drought, Zn, and combination D + Zn stress treatments increased proline accumulation (p < 0.0001), antioxidant enzyme activities (p < 0.05), including superoxide dismutase (SOD), ascorbate peroxidase (APX), glutathione reductase (GR), and decreased levels of MDA. Overall, these responses indicate that the Miscanthus GRC10 hybrid displays a complex response to drought and Zn stresses that confers growth resilience in Zn-contaminated and drought-prone lands.